Oculomotor behavior and perceptual strategies in complex tasks - Pelz, Jeff B; Canosa, Roxanne (Vision research (Oxford), 2001)
While we know a great deal about the dynamics and characteristics of eye movements in relatively simple tasks performed under reduced laboratory conditions, we know less about oculomotor behavior in complex, multi-step tasks. Complex tasks are not necessarily difficult. Part of the transition from ‘hard’ to ‘easy’ in completing complex tasks is the gradual reduction in conscious effort required to complete the sub-tasks. We are interested in learning whether high-level perceptual strategies can aid that transition. In the past, subjects performed relatively simple tasks or the eye movements themselves were the instructed task. But outside the laboratory vision is a tool, not the task. To study the oculomotor system in its native mode, we developed a wearable eyetracker that allows natural eye, head and whole-body movements. Using the over-learned, common task of hand-washing, we measured the global characteristics of fixation duration, saccade amplitude, and the spatial distribution of fixation positions. An important observation was the emergence of higher-order perceptual strategies in the complex task: while most fixations were related to the immediate action, a small number of fixations were made to objects relevant only to future actions. Based on a control task that differed only in the high-level goal, we conclude that the look-ahead fixations represent a task-dependent strategy, not a general behavior elicited by the salience or conspicuity of objects in the environment. We propose that the strategy of looking ahead to objects of future relevance supports the conscious percept of an environment seamless in time as well as in space.